2015
DOI: 10.1111/ced.12650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycophenolic acid on proliferation of dermal papilla cells and induction of anagen hair follicles

Abstract: MPA promotes proliferation of DPCs and induction of anagen hair follicles in mice. This finding raises the possibility that MPA could be used as a treatment option for hair-loss disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In addition, various other compounds have demonstrated stimulatory effect on DPCs at molecular level .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…In addition, various other compounds have demonstrated stimulatory effect on DPCs at molecular level .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…In another animal study assessing the hair growth effect of mycophenolic acid (MP), microneedling was found to accelerate the stimulatory growth of topical MP on anagen follicles [48].…”
Section: Evidence For Efficacymentioning
confidence: 99%
“…The protocol for western blot analysis was described in a previous report 9 . Briefly, protein lysates from hDPCs were prepared using radio immunoprecipitation assay cell lysis buffer containing protease inhibitor cocktail.…”
Section: Western Blot Analysismentioning
confidence: 99%